USER PERCEPTIONS ABOUT THE QUALITY OF INFORMATION SYSTEMS IN PUBLIC UNIVERSITIES: A CASE STUDY AT UFRRJ - Garcia, Daniel Romanini; da Motta, Rosa Amelita Sá Menezes; de Oliveira, Saulo Barbará; de Oliveira, Altemar Sales; Coelho Júnior, João Batista Lopes; Inácio, Diego Ramos; de Carvalho Saraiva, André Ricardo (Seven Editora, 2025)
This article addresses the perceptions of users of information systems at the Federal Rural University of Rio de Janeiro (UFRRJ), focusing on assessing the quality of the SIGAA, SIPAC, and SIGRH systems. This quantitative-qualitative and exploratory research was based on the criteria of the ISO/IEC 25010 quality model. The objective was to analyze the perceptions of students, faculty, and technical-administrative staff regarding the quality characteristics of the systems, in order to generate an evaluative opinion on their customization and usability. The results, focused on SIGAA, indicate that, for most users, the system is functionally adequate, but presents serious deficiencies in stability and performance during periods of high demand, such as enrollment. There is also a widespread perception of the need for improvements in the graphical interface and information organization. Continued research is essential to analyze other systems and deepen the understanding of the needs of the academic community, aiming to contribute to the university's Information and Communication Technology Coordination (COTIC).DOI: https://doi.org/10.56238/sevened2025.029-088